Tinjauan Terhadap Status Hubungan Kerja Pekerja yang Diperbantukan di Perusahaan Lain: Studi Pertamina Group - Julianto; Hosein, Siti Hajati (WARKAT, 2025)
This research aims to analyze the arrangements related to the employment relationship of workers who are seconded to other companies, the implementation of the employment relationship of workers who are seconded to other companies by taking a study at Pertamina Group, as well as the ideal arrangements related to the employment relationship status of workers who are seconded to other companies. The method used is normative juridical research method with qualitative data type. The results of the study show that the existence of a regulatory vacuum causes the non-achievement of legal certainty as one of the objectives of the law. Moreover, until now the Manpower Law has not explicitly regulated worker assistance. The government needs to strengthen labor regulations related to secondment of workers, including regulating the terms of secondment of workers, secondment agreements, protection of the rights of secondment workers, and settlement of industrial relations disputes of secondment workers. Secondment agreements that have been implemented by several companies, one of which is PT Pertamina (Persero), can be the basis for current arrangements related to worker secondment. In the secondment agreement, arrangements are made that as long as workers are seconded to other companies, there will be no transfer of employment relations from the home company to the user company. In addition, it also regulates the period of assistance and the rights of workers during the period of assistance, which are guaranteed at least the same as the rights of workers when working in the original company.